Wayside testing methods for high-frequency vertical wheel-rail impact forces and its applicability. (February 2020) - Bi, Lanxiao; Zhao, Pingrui; Teng, Mingzhi; Zhao, Lin; Liu, Xueyi; Xing, Mengting
Highlights: Two strain-based testing methods can identify high-frequency wheel–rail impact force. The accuracy and application scope of each measurement method are obtained. The accuracies of all measurement methods decrease obviously at rail joints. The relation between the layout and the effective measurement length is clarified. Abstract: Methods for measuring high-frequency wheel–rail impact forces are indispensable in the study of railway vehicle dynamics. Although there have been many methods proposed for impact force measurement, not all of them are accurate at high-frequencies. Additionally, most of the proposed measurement methods are quasi-static methods that require static calibration. Therefore, the accuracy and applicability of different high-frequency wheel–rail force measurement methods need to be studied and validated dynamically. In this paper, a refined numerical track structure model is constructed to simulate wheel–rail impact behaviors. Under dynamic loading conditions, compare the 'equivalent value' and 'actual value' of wheel-rail impact forces using different wayside testing methods. The simulation results are then dynamically verified using full-scale indoor test results. The rules dictating effective strain gauge arrangement and the application scope of each measurement method are then obtained, and the relationship between the layout of the strain gauges and the effective measurement length is clarified. The results of this study indicate that the high-frequency wheel–rail impact force measured on site is generally underestimated, and because rail joint splints change the supporting conditions of the rail, the accuracies of all high-frequency wheel–rail impact force measurement methods decrease obviously at such rail joints.